Les aventures du narratif dans deux romans de Pierre Senges - Kroker, Wiesław (Wydawnictwo Naukowe UAM, 2013)
In his novels, Pierre Senges (born in 1968) constantly questions the limits of the literary representation as he emphasizes the textual nature of any fictional world. "Veuves au maquillage" (2000) is a relatively continuous narrative of an unusual suicide planned by the protagonist-narrator as a methodic murder gradually committed on him by his six mistresses, the six jealous widows; whereas "Études de silhouettes" (2010) consists of a series of short texts, each based on a phrase from Kafka’s drafts, without any thematic bounds between them. In Senges’s universe, the borders become blurred between different possible worlds so as the reader does not get the possibility to determine whether any of these worlds has a priority over the others. His postmodern writing is a lesson and a practice of relativity of values and significations.
Adventures of the narrative in two novels by Pierre Senges
Keywords: fiction; representation; postmodern writing; textuality; possible worlds; relativity of values